DOCKING STUDIES FOR VARIOUS ANTIBACTERIAL BENZILATE DERIVATIVES - R, SUDHA; P, Brindha Devi; Kanakam, Charles C; G, Nithya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: In this study, we have focused on discovering the leads for the enzyme targets of infectious disease tuberculosis. We employed computeraidedÂ drug design docking tool,to discover new leads for Mycobacterium tuberculosis (MTB). Methods: Five compounds were synthesized and they are made to dock into the active site of the enzyme; retrieved from protein data bank. Results: The docking studies and structureâ€“activity relationship reveals that the compound 2'-chloro-4-methoxy-3nitro benzilic acid after three different docking strategies reveals that the score was found to be higher compared with others(âˆ’5.568 kcal/mol). Conclusion: On the closer analysis of this molecule, the molecule showed stacking interaction and the compound has also found to be surrounded byÂ non-polar amino acids, which makes this molecule potent toward antibacterial drug discovery. Keywords: Antibacterials, Docking, Absorption, Distribution, Metabolism and excretion study, Resistance.